Optimizing the role of the Ngudi Peni Waste Bank to improve environmental cleanliness - Syahara, Tjut Afrieda; Ardiansyah, Galang; Alkhoroni, Panji; Fatimah, Siti; Ningsih, Mulati; Susanti, Dwi (Community Empowerment, 2021)
The environmental issue that has received the most attention from the world in the last few decades is global warming. Global warming is directly related to the amount of waste produced by humans, so waste reduction must be carried out by all levels of society. The method of reducing waste using the 3R system (Reuse, Reduce and Recycle) has not had a significant impact. Another alternative that can be applied is to create a waste bank. One of them is the Ngudi Peni Waste bank in Gupitan Village, Candimulyo District, Magelang Regency. This method of saving with waste is expected to have an economic impact on the community. This service activity used several methods, namely socialization, training, and assistance for the management of the Ngudi Peni Waste Bank. The results obtained from this service activity include the formation of the Ngudi Peni Waste Bank organizational structure, the creation of a waste catalog and administrative steps for waste management. In addition, effective promotion and communication media are also produced through social media and Public service Advertisement.